(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the results of practical translation lessons held at the Department of "Japanese Philology" of the Higher School of Japanese Studies of the Tashkent State University of Oriental Studies. The object of the research is the work "Taketori Monogatari" ("The Tale of the Bamboo Cutter"), which is considered the oldest written monument of Japanese classical literature and dates back to the Heian period. The article emphasizes the lexical and semantic features of translation from classical Japanese (kobun) into Uzbek by 3rd-year students, the transmission of symbolic images and cultural realities, as well as the linguodidactic significance of working on the text.